Treatment Outcomes of Patients Switching From an Injectable Drug to Bedaquiline During Short Standardized Treatment for Multidrug-resistant Tuberculosis in Mozambique. (11th March 2019) - Bastard, Mathieu; Molfino, Lucas; Mutaquiha, Cláudia; Galindo, Miriam Arago; Zindoga, Pereira; Vaz, Deise; Mahinça, Ivan; DuCros, Philipp; Rusch, Barbara; Telnov, Alex
Abstract: Bedaquiline was recommended by the World Health Organization as the preferred option in treatment of multidrug-resistant tuberculosis (MDR-TB) with long regimens. However, no recommendation was given for the short MDR-TB regimen. Data from our small cohort of patients who switched from injectable drug to bedaquiline suggest that a bedaquiline-based short regimen is effective and safe.